Estimation of genetic parameters and breeding values for growth traits using random regression model in Landrace × desi crossbred pigs - CHAUDHARY, RAJNI; PRAKASH, VED; SAILO, LALRENGPUII; SINGH, AKANSHA; KARTHIKEYAN, A; BASHIR, AAMIR; MONDAL, S K; SAHOO, N R; KUMAR, AMIT (The Indian Journal of Animal Sciences, 2019)
The experiment was conducted to estimate genetic parameters and breeding value of pre-weaning and postweaning growth traits in Landrace × Desi (indigenous) crossbred pigs. Random regression model (RRM) with fixed effects, random effects of direct additive, maternal genetic, maternal permanent environmental and individual permanent environmental effects and a heterogeneous residual variance structure over growth measurement at different time point was applied to estimate the genetic parameters. Among different order of Legendre polynomial fitted, RRM with heterogeneous error variance (RRMâ€“HET) with fourth order fit for direct genetic, maternal genetic and maternal permanent environmental effect and third order fit for individual permanent environmental effect was found as the best model. The direct genetic heritability estimates were 0.299Â±0.021 at birth, which was low (0.011Â±0.006) at W12 and high at W36 (0.582Â±0.03). The first eigenvalue accounted for more than 98% variation in body weight and the corresponding trajectories had positive values displaying almost linear pattern till weaning and then increased rapidly in post weaning age. This showed that the selection of pigs on the basis of mean body weight at early age can also result in higher body weight in post-weaning stages. The average breeding value for the birth weight, W8 and W32 was 0.951 kg, 10.162 kg and 49.598 kg, respectively. The 42.86% of sire population at W12 and 56.76% at W24 had breeding value higher than the population’s mean breeding value indicating existence of genetic variation and thus the scope for increasing the selection pressure.